Estructura horizontal y distribución diamétrica de un bosque de colina baja, distrito de San Pablo, Loreto, Perú. 2024 - Rios Soria, Grace Adriana (2025)
An analysis was carried out on the horizontal structure and the diameter distribution of a low hill forest located in Cutting Plot 1 (PC 1), belonging to the of a low hill forest located in Cutting Plot 1 (PC 1), belonging to the General Plan of Forest Management (PGMF). No. 16-LOR-MAR/CON-MAD-2024-01, in the district of San Pablo. During the 737 trees were recorded during the forest inventory, grouped into 35 species of 19 botanical families. Botanical families. Cedrelinga cateniformis was identified as the most significant species in ecological terms, with an index of ecological The most ecologically significant species was identified as Cedrelinga cateniformis, with an index of importance value of 16.39%, followed by Virola loretensis, with an index of 14.19%. of 14.19%. The data revealed that the highest concentration of trees is found in the intermediate diameter classes. The data revealed that the highest concentration of trees is found in the intermediate diameter classes, with the 30 cm class standing out with a density of 121 trees per hectare. Cm with a density of 121 trees per hectare. In contrast, the extreme classes in contrast, the extreme classes, such as 10 cm and 80 cm or more, had much lower densities, with 24.5 and 27 trees per hectare. And 27.6 trees per hectare, respectively, were much lower, with 24.5 and 27.6 trees per hectare. These These results support the hypothesis put forward in the study, showing that the horizontal structure of the the horizontal structure of the forest is characterized by a high density of tree species, while the horizontal tree species, while the diametric distribution indicates a remarkable diversity in the diameter diversity in tree diameter sizes.